Trastuzumab deruxtecan (DS-8201) plus bevacizumab for HER2-low metastatic breast cancer with malignant pleural effusion: a case report and literature review - Han, Hao; Liu, Jing; Wang, Congcong; Yang, Miaomiao; Liu, Jiannan; Sun, Ping (Frontiers in Oncology, 2026)
IntroductionHER2-low breast cancer has emerged as a distinct molecular subtype with unique biological features and therapeutic significance. Trastuzumab deruxtecan, an antibody-drug conjugate, has shown promising efficacy in both HER2-high and HER2-low disease.Case descriptionWe report the case of a 69-year-old woman with a 17-year history of breast cancer, initially diagnosed in 2007 with invasive ductal carcinoma and lymph node metastasis. After multiple lines of systemic therapy, the disease progressed with dynamic reduction of HER2 expression from 3+ to 1+, ultimately confirming HER2-low advanced breast cancer. Recurrent malignant pleural effusion became the predominant manifestation, severely impairing quality of life.Intervention and outcomesDS-8201 monotherapy was initiated but failed to control pleural effusion. Sequential combinations of DS-8201 with intrapleural cisplatin and then intrapleural bevacizumab were attempted, with only the latter yielding significant benefit. The regimen was subsequently optimized to intravenous DS-8201 plus bevacizumab, resulting in rapid symptom relief, substantial reduction of pleural effusion, and sustained disease control. At the latest follow-up, the patient achieved 18 months of stable disease with improved quality of life and no severe adverse events.ConclusionTo our knowledge, this is the first reported case of DS-8201 plus bevacizumab for HER2-low metastatic breast cancer with malignant pleural effusion. This case highlights the potential of this regimen as a promising therapeutic option for patients with limited alternatives.